Werken van Michiel De Swaen : 1. De Tooneelspelen: deel 1 - Huysmans, Camille; Celen, V. (Antwerpen : De Sikkel, 1928)
Bibliotheek E. Anseele
Genummerd ex. 16
Nederlands
Meerdelige publicatie
Keywords: toneel